1999
DOI: 10.1523/jneurosci.19-06-02301.1999
|View full text |Cite
|
Sign up to set email alerts
|

A Glial Cell Line-Derived Neurotrophic Factor-Secreting Clone of the Schwann Cell Line SCTM41 Enhances Survival and Fiber Outgrowth from Embryonic Nigral Neurons Grafted to the Striatum and to the Lesioned Substantia Nigra

Abstract: We have developed a novel Schwann cell line, SCTM41, derived from postnatal sciatic nerve cultures and have stably transfected a clone with a rat glial cell line-derived neurotrophic factor (GDNF) construct. Coculture with this GDNF-secreting clone enhances in vitro survival and fiber growth of embryonic dopaminergic neurons. In the rat unilateral 6-OHDA lesion model of Parkinson's disease, we have therefore made cografts of these cells with embryonic day 14 ventral mesencephalic grafts and assayed for effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 62 publications
5
55
1
4
Order By: Relevance
“…GDNF is highly expressed in the developing rat striatum, yet its concentration is relatively low in the adult brain (Choi-Lundberg and Bohn, 1995;Schaar et al, 1993;Stromberg et al, 1993). Several studies in the 6-hydroxydopamine (6-OHDA) lesioned striatum of rats have demonstrated improvements in survival and outgrowth of grafted fetal DA neurons when central injections of GDNF have been administered, or when GDNF overexpressing cells have been co-grafted to the striatum (Ahn et al, 2005;Espejo et al, 2000;Rosenblad et al, 1996;Sautter et al, 1998;Sinclair et al, 1996;Sullivan et al, 1998;Wilby et al, 1999;Yurek, 1998). These effects of GDNF on grafted VM were evaluated 1 to 8 weeks after transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…GDNF is highly expressed in the developing rat striatum, yet its concentration is relatively low in the adult brain (Choi-Lundberg and Bohn, 1995;Schaar et al, 1993;Stromberg et al, 1993). Several studies in the 6-hydroxydopamine (6-OHDA) lesioned striatum of rats have demonstrated improvements in survival and outgrowth of grafted fetal DA neurons when central injections of GDNF have been administered, or when GDNF overexpressing cells have been co-grafted to the striatum (Ahn et al, 2005;Espejo et al, 2000;Rosenblad et al, 1996;Sautter et al, 1998;Sinclair et al, 1996;Sullivan et al, 1998;Wilby et al, 1999;Yurek, 1998). These effects of GDNF on grafted VM were evaluated 1 to 8 weeks after transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its action on DA neuron survival, GDNF also stimulates outgrowth of DA neurons after lesion or grafting in the rodent (Sinclair et al, 1996;Sautter et al, 1998;Wilby et al, 1999;Zhang et al, 2013) and NHP brain Redmond Jr. et al, 2009;Wakeman et al, 2014). Combination of GDNF and NETRIN-1 was found to support directed long-distance growth of DA axons from rodent fVM grafts .…”
Section: Axonal Outgrowth and Migration In The Host Brainmentioning
confidence: 97%
“…Despite the fact that most reviews of transplants for PD mention this point (e.g., [155]), to our current knowledge, despite several apparent successes in establishing nigra-to-striatum re-innervation from nigral dopaminergic grafts [159][160][161][162][163][164][165], there have been no systemic assessments of the afferent control of these grafts established by the host. Clearly the main interest at present with such a grafting strategy is to ensure the dopaminergic reconstruction extends across the inhospitable terrain of the adult brain from the nigra to the striatum.…”
Section: Adaptation Of Transplanted Neural Cells To the Endogenous Homentioning
confidence: 99%
“…These GABAergic transplants into the nigra also may contribute benefit by increasing the local suppression of noise as described previously for the seemingly noisy striatum. As efforts expanded, it became clear that considerable neurotrophic support was necessary and this was either provided by "bridge" tissue grafts that might be likely to release such compounds, such as Schwann cell type cells, or the local cells were induced to release these compounds by viral transgenic expression (e.g., [82,160,170]). This strategy renders the CNS territory through which the new dopaminergic fibers must grow more hospitable, presumably also providing retrograde support signals, inspiring continued growth, and staving off the previously-described cell death that results from the lack of connectedness during this growth journey.…”
Section: Adaptation Of Transplanted Neural Cells To the Endogenous Homentioning
confidence: 99%